Orthogonally protected cyclohexanehexols by a ``one reaction - one product'' approach: efficient access to cyclitols and their analogs - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
Differentially protected myo-inositol derivatives were prepared from commercially available myo-inositol through regioselective O-alkylation reactions, which give a single product in each step. These derivatives were converted into six isomeric inositol derivatives carrying orthogonal hydroxy protecting groups. For all these reactions, conditions were chosen to prevent the formation of isomeric products, which obviates the need for separation of isomers and provides the required cyclitol derivative in very good yields. The synthetic potential of these derivatives was illustrated by the conversion of some of the orthogonally protected inositol derivatives into other cyclitol derivatives. Isomeric inositols were also prepared by the global deprotection of all the hydroxy groups.
Keywords: Alkylation; cyclitols; Inositol; Protecting groups; Regioselectivity